Pacemaker dependence in patients with bifascicular block during acute anterior myocardial infarction. Issue 4 (October 1984) - Edhag, O; Bergfeldt, L; Edvardsson, N; Holmberg, S; Rosenqvist, M; Vallin, H
Abstract : Eleven patients with bifascicular block complicating anteroseptal acute myocardial infarction were studied to determine the effect of prophylactic permanent pacing; eight of them also had transient high grade atrioventricular block during the acute phase of the infarction. One month after the infarction an electrophysiological study was performed and a bradycardia indicating pacemaker implanted. All the patients were followed for two years. Six had bradycardia detected, two of whom did not have high grade atrioventricular block during the index infarction. Seven patients died, four of them suddenly. There was no correlation between the electrophysiological findings and subsequent development of bradycardia. Thus pacemaker dependence seems to be common in patients with bifascicular block complicating acute myocardial infarction. Mortality is, however, also high in patients treated with pacemakers. Prospective studies to determine the predictive factors in those patients with an anterior acute myocardial infarction and who benefit from a combination of permanent pacemaker treatment and antiarrhythmic treatment are needed.